PERDA SYARIAH DALAM TINJAUAN KONSTITUSI, FAKTA SEJARAH DAN AQIDAH ISLAM - Ali Musri Semjan Putra (Al-Majaalis : Jurnal Dirasat Islamiyah, 2019)
There are two sides of view that need to be compromised, groups that carry radical, extremist and secular, liberal and nationalist groups. Each of them mutually clasps the one-sided truth, as if the religious and nationalist circles are two angles of a triangle that would not be possible to find. Nationalists view that the application of sharia regulations is an effort to place Muslims as an exclusive and special community in this country and place other people as second-class citizens. On the other hand radicals consider that the current system of government is in contradiction with the Islamic range absolutely, total and radical changes must be made.So this research tries to open the discourse of moderate thinking in addressing this problem, not extreme left and not right extreme. The main subject of this study will be based on three issues, sharia regulations in constitutional review, historical facts about the application of Shari'ah on Nusantra and sharia law in the review of Islamic Aqeedah. This study was conducted in the form of literary literature studies using the induction approach using qualitative analysis.The conclusion of this study, that the application of sharia regulations is part of actualizing constitutional orders into real life. Part of sharia law is valid in the unitary State of the Republic of Indonesia. Doing radical methods such as coups and for example in attempting to adopt sharia law is contrary to sharia law itself.